Relaciones y tensiones entre lo urbano y lo rural - Martínez Godoy, Diego; Martínez Godoy, Diego (Serie Territorios en debate, 2017)
The third world conference of the United Nations for Habitat, held in Quito in October 2016, showed that currently the concerns of authorities of international organizations, government, public policy managers and planners, are still focused, in their the great majority, in urban problems without taking into account the existing relations with the space as a whole which also has rural spaces and at the same time spaces produced by the interaction of urban and rural areas. On the one hand, this makes it impossible to reflect on the possible consequences of urban development policies in the different territories shaped and historically constructed from this conjugation of urban-rural articulations. And on the other hand it does not allow to account for the potentialities coming from logics of territorial cooperation between both types of spaces. To what extent are urban-rural relationships ignored? What can be the consequences? How can we come to rethink the new relationships and interactions between the countryside and the city to favor the construction of solid processes of territorial development in the 21st century?